PENERAPAN METODE CASE BASED REASONING DALAM KLASIFIKASI KEPRIBADIAN SISWA DI SMP NEGERI 27 SELUMA - Rahmat Aditya Yansyar; Siswanto Siswanto; Lena Elfianty (Smart Education, 2024)
Abstract: SMP Negeri 27 Seluma is a Junior High School located in Seluma Regency, Bengkulu Province. SMP Negeri 27 Seluma in order to achieve success student so that they have noble character, educators and parents need to understand one important aspect in educating students, namely identifying their personality first. This will make it easier to take the next steps in educating children so they can apply life values well. However, limited space and time for parents makes it difficult for them to consult directly with an expert or psychologist. The implementation of Case Based Reasoning Method in the classification students’ personalities at SMP Negeri 27 Seluma was created to serve as a tool in making it easier to find out the personality type of each student at SMP Negeri 27 Seluma based on the characteristics of each student. The system has implemented of Case Based Reasoning Method where the characteristics of each student are multiplied by the weight of characteristics of each personality type, then look at the highest percentage value of each personality type to get the final result of the classification of each student's personalities type. Based on the results of the tests that have been carried out, the functionality of the students’ personalities in classification application at SMP Negeri 27 Seluma has run well as expected and is able to provide information on the results of the personality type classification for each student per academic year. Keywords: Case Based Reasoning Method, Students’ Personalities Classification, SMP Negeri 27 Seluma. Abstrak: SMP Negeri 27 Seluma merupakan Sekolah Menengah Pertama Negeri yang terdapat di Kabupaten Seluma Provinsi Bengkulu. SMP Negeri 27 Seluma dalam mencapai keberhasilan siswa agar memiliki budi pekerti yang luhur, maka pendidik dan orang tua perlu memahami salah satu aspek penting dalam mendidik siswa yaitu mengidentifikasi kepribadian mereka terlebih dahulu. Hal ini akan memudahkan pengambilan langkah selanjutnya dalam mendidik anak supaya dapat menerapkan nilai-nilai kehidupan dengan baik. Namun terbatasnya ruang dan waktu bagi orang tua menyebabkan mereka kesulitan dalam melakukan konsultasi langsung kepada seorang pakar atau ahli psikologi. Penerapan Metode Case Based Reasoning dalam klasifikasi kepribadian siswa di SMP Negeri 27 Seluma dibuat untuk dijadikan sebagai alat bantu dalam mempermudah mengetahui tipe kepribadian setiap siswa di SMP Negeri 27 Seluma berdasarkan ciri-ciri dari setiap siswa tersebut. Pada sistem telah diterapkan Metode Case Based Reasoning dimana ciri-ciri setiap siswa akan dikalikan dengan bobot ciri-ciri pada setiap tipe kepribadian, kemudian melihat nilai persentase tertinggi dari setiap tipe kepribadian untuk mendapatkan hasil akhir klasifikasi tipe kepribadian setiap siswa. Berdasarkan hasil pengujian yang telah dilakukan, fungsional dari aplikasi klasifikasi kepribadian siswa di SMP Negeri 27 Seluma telah berjalan dengan baik sesuai yang diharapkan dan mampu memberikan informasi hasil klasifikasi tipe kepribadian setiap siswa per tahun ajaran Kata kunci: Metode Case Based Reasoning, Klasifikasi Kepribadian Siswa, SMP Negeri 27 Seluma